(untitled) (Research, Society and Development, 2021)
Microorganisms are a biotechnological alternative to optimize plant productivity in a globally sustainable way, reducing the use of chemical products and environmental impacts. Microbial inoculants, such as rhizobacteria (plant growth promoting rhizobacteria - PGPR), mycorrhizae and fungi can be inoculated in seeds, roots, soil or leaves. Plant growth-promoting microbes (PGPM) improve plant growth by direct action, such as biostimulants and biofertilizers, and indirectly as biocontrol. Microbial biotechnology is beneficial because it accelerates plant growth, increases productivity and nutritional quality of foods, in addition to increasing plant tolerance against biotic and abiotic stresses. Considering that microorganisms have great potential as biopromoters, knowing the PGPM-plant interaction will result in greater success in microbial biotechnology. Thus, this review aims to address how inoculation methods can interfere in PGPM-plant interaction, elucidating the mechanisms of microbial biotechnology and benefits to plants.